Sammlung Hahn : Museum Moderner Kunst Wien. - Cladders, Johannes (Wien : Gesellschaft der Freunde des Museum Moderner Kunst Wien, 1979)
Aeppli, Eva ; Alvermann, Hans Peter ; Anatol ; Anouj ; Arman ; Ay-O ; Baj, Enrico ; Beckley, Bill ; Al Bengston, Billy ; Beuys, Joseph ; De Boer, Saskia ; Brecht, George ; Brock, Bazon ; Broodthaers, Marcel ; Brusse, Mark ; Bury, Pol ; Buthe, Michael ; Canonico, Felix ; César ; Chamberlain, John ; Christo ; Copley, William N. ; etc.
Duits
boek